Behavioural effects of novel multitarget anticholinesterasic derivatives in Alzheimer's disease. Issue 2 (April 2017) - Giménez-Llort, Lydia; Ratia, Miriam; Pérez, Belén; Camps, Pelayo; Muñoz-Torrero, Diego; Badia, Albert; Clos, M. Victoria
Abstract : The current pharmacological approach to Alzheimer's disease (AD) treatment, mostly based on acetylcholinesterase inhibitors (AChEIs), is being revisited, especially in terms of the temporal frames and the potential benefits of their noncanonic actions, raising the question of whether inhibitors of AChE might also act in a disease-modifying manner. Besides, in the last decades, the pharmacophoric moieties of known AChEIs have been covalently linked to other pharmacophores in the pursuit of multitarget hybrid molecules that are expected to induce long-lasting amelioration of impaired neurotransmission and clinical symptoms but also to exert disease-modifying effects. Our research consortium has synthesized and defined the pharmacological profile of new AChEIs derivatives of potential interest for the treatment of AD. Among these, huprines and derivatives have been characterized successfully. Huprine X, a reversible AChE inhibitor, designed by molecular hybridization of tacrine and huperzine A, has been shown to affect the amyloidogenic process in vitro, and the AD-related neuropathology in vivo in mice models of the disease. More recently, we have shown that a group of donepezil–huprine heterodimers exerts a highly potent and selective inhibitory action on AChE both in vitro and ex vivo, simultaneously interacting with both peripheral and catalytic binding sites, and inhibiting the β-amyloid aggregation, whereas some levetiracetam–huprine hybrids have been shown to reduce epileptiform activity, neuroinflammation and amyloid burden in an animal model of AD. Here, we summarize the behavioural correlates of these noncanonic actions as assessed in three distinct biological scenarios: middle-age, cognitive deficits associated with ageing and AD-like phenotype in mice. Besides the improvement in the hallmark cognitive symptomatology without inducing side effects, these drugs have shown to be able to modulate emotional and anxiety-like behaviours or to reduce spontaneous seizures, all of them related to the so-called 'behavioural and psychological symptoms of dementia'. Overall, the studies show that these novel multitarget anticholinesterasics exert noncanonic actions providing symptomatic and disease-modifying benefits of potential interest for the management of AD.